School of magical animals [videorecording (DVD)] - Schmidt, Viola; Chambers, John; Maier, Emilia; Conrads, Leonard; Sichrovsky, Loris; Auer, Margit, 1967- (Breaking Glass Pictures, 2023)
Ida must transfer to a new school, where she soon realizes the students are unkind to each other. However, that all changes when a new teacher, Miss Cornfield, begins to educate them on the value of friendship and magic.